Teknologi diujung Jari, Bahaya dibaliknya: Sosialisasi Hukum tentang Judi Online bagi Masyarakat Desa - Taufik, Zahratul'ain; Mulyana, Septira Putri; Raodah, Putri; Rahmania, Nunung; Nirmala, Atika Zahra; Ashady, Suheflihusnaini (Universitas Pahlawan Tuanku Tambusai, 2026)
The development of digital technology has brought tremendous convenience to various aspects of human life, ranging from work and education to lifestyle transformation. However, this advancement also opens opportunities for the misuse of technology, one of which is the rising phenomenon of online gambling that has become increasingly prevalent and difficult to control. This issue not only affects urban communities but has also spread to rural areas, including housewives and adolescents, who are particularly vulnerable to the negative impacts of the internet. This community service activity aimed to increase the legal awareness of the residents of Korleko Selatan Village regarding the dangers of online gambling from legal, social, and psychological perspectives. The method used was descriptive qualitative with an educational and participatory approach, in which the community actively participated in socialization sessions, discussions, and question-and-answer activities. The results showed an improvement in participants’ legal understanding and digital awareness concerning the impacts and legal consequences of online gambling. Moreover, this activity fostered a stronger community commitment to using technology wisely and avoiding illegal activities in the digital space.